Climate risk: The price of drought - Huynh, Thanh D.; Nguyen, Thu Ha; Truong, Cameron (Journal of Corporate Finance, 2020)
We document a significant positive relation between drought risk and the cost of equity capital. Our estimation shows that the cost of equity capital is 92 basis points higher for firms affected by severe drought conditions. We provide evidence that when firms are affected by droughts, firms with higher local institutional holdings exhibit a higher cost of equity capital. This result supports the well-known local bias of institutional investors, and suggests that diversification cannot fully eliminate the loss in wealth caused by droughts. Consistent with theoretical predictions, we find that drought duration and drought intensity further increase a firm's risk premium. However, for firms with diversified cash flows/investments, geographically dispersed business operations, and high cash holdings, the impact of drought on the expected return is significantly lessened. Overall, our findings show that investors require a higher rate of returns on firms affected by droughts and offer implications on how firms can mitigate the impact of droughts on their cost of capital.